1999
DOI: 10.1086/314376
|View full text |Cite
|
Sign up to set email alerts
|

Lode Gold Deposits and Archean Mantle Plume–Island Arc Interaction, Abitibi Subprovince, Canada

Abstract: In combination with seismic interpretations and geochronological constraints, the association of juvenile arc-type low-Ti tholeiitic basalts with komatiites in the southeastern Abitibi subprovince, Canada, supports a history of subduction step back following Late Archean mantle plume-island arc interaction. The resulting paired collision zones preserved abundant komatiites and numerous massive sulphide deposits and established the critical metallogenic features to concentrate the majority of Canada's Precambri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(10 citation statements)
references
References 37 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…At least in the Phanerozoic, processes such as ridge subduction, slab roll-back, and SCLM erosion are associated with asthenospheric upwelling, high geothermal gradients, and regional metamorphism. In the Precambrian, specifics of formation and evolution of auriferous greenstone belts remain controversial, but involvement of plume episodes on the hotter Earth were clearly critical (e.g., were active in the Precambrian (e.g., Wyman et al, 1999;Wyman and Kerrich, 2010), although the SCLM keels below the cratons and lack of clear Cordilleran-type orogenic belts indicates some important differences.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…At least in the Phanerozoic, processes such as ridge subduction, slab roll-back, and SCLM erosion are associated with asthenospheric upwelling, high geothermal gradients, and regional metamorphism. In the Precambrian, specifics of formation and evolution of auriferous greenstone belts remain controversial, but involvement of plume episodes on the hotter Earth were clearly critical (e.g., were active in the Precambrian (e.g., Wyman et al, 1999;Wyman and Kerrich, 2010), although the SCLM keels below the cratons and lack of clear Cordilleran-type orogenic belts indicates some important differences.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Precambrian deposits appear to have formed also in similar tectonic settings of anomalously high thermal energy (e.g., Kerrich and Cassidy, 1994;Qiu and Groves, 1999;Wyman et al, 1999). Thus, orogenic gold deposits of all ages record orogen-wide fluxes of deeply sourced heat and fluid as part of the orogenic process in convergent margins (e.g., Fyfe and Kerrich, 1985), almost certainly in response to global-scale tectonic events.…”
Section: Tectonic Evolution and Secular Change In Metallogeny: Messagmentioning
confidence: 99%
“…There is a possibility that some of the shear zones of gold mineralization may penetrate to the depth of the mantle (Kerrich et al, 2000). The world class gold deposits of Abitibi belt are probably formed through a process of mantle plume-island arc accretion (Barley et al, 1998;Wyman et al, 1999), suggesting that the source of the gold bearing fluids may anywhere from mantle to crust (Santosh, 1993). Based on the Δ 33S signature of sulfur in four Archean orogenic gold deposits, Xue et al (2013) have suggested a granitic source for hydrothermal fluids.…”
Section: Discussionmentioning
confidence: 99%